Functional disruption of cerebello-thalamo-cortical networks in obsessive compulsive disorder - Sha, Zhiqiang (Biol Psychiatry Cogn Neurosci Neuroimaging, 2019)
BACKGROUND: Obsessive-compulsive disorder(OCD) is characterized by intrusive thoughts and repetitive, compulsive behaviors. Neuroimaging studies have implicated altered connectivity among the functional networks of the cerebral cortex in the pathophysiology of OCD. There has, however, been no comprehensive investigation of the cross-talk between the cerebellum and functional networks in the cerebral cortex. METHODS: Forty-four adult participants with OCD and 43 healthy participants completed this functional neuroimaging study. We performed large-scale data-driven brain network analysis to identify functional connectivity patterns using resting-state functional magnetic resonance imaging data. RESULTS: OCD participants showed lower functional connectivity within the somatomotor network and greater functional connectivity among the somatomotor network, cerebellum and subcortical network(e.g. thalamus and pallidum, all Ps<0.005). Network-based statistics analyses demonstrated one component comprising connectivity within the somatomotor network that showed lower connectivity, and a second component comprising connectivity among the somatomotor network, and motor regions in particular, and the cerebellum that showed greater connectivity, in OCD relative to healthy participants. In OCD participants, abnormal connectivity across both network-based statistic-derived components positively correlated with OCD symptom severity(P=0.006). CONCLUSIONS: To our knowledge, this study is the first comprehensive investigation of large-scale network alteration across the cerebral, subcortical regions and the cerebellum in OCD. Our findings highlight a critical role of the cerebellum in the pathophysiology of OCD.